Suap (Risywah) untuk Mempertahankan Hak Milik dalam Perspektif Imam al-Nawawī: Bribery (Risywah) to Maintain Ownership in the Perspective of Imam al-Nawawī - Muhamad Saddam Nurdin; Hendra Wijaya; Ahmad Abdullah; Muttazimah, Muttazimah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
Bribery (risywah) is a widespread issue affecting various aspects of life, such as law, economics, and education, and it contradicts the norms of decency and the moral principles of Pancasila. In both Islamic law and Indonesian positive law, bribery is considered haram, although some scholars provide exceptions for preserving property rights. Generally, bribery is forbidden and must be avoided, as it can harm the rights of others and society. This study aims to examine Imam al-Nawawī's view on the legality of bribery to protect property rights. The research employs a descriptive qualitative method with a library research approach, focusing on the study of manuscripts and texts, using normative and conceptual approaches. The findings reveal two scholarly opinions: first, scholars have two views on bribery: it is either absolutely forbidden or forbidden with certain exceptions. Second, Imam al-Nawawī argues that bribery to protect property rights is permissible under emergency conditions, similar to paying ransom to free Muslim captives. The implications of this study contribute to contemporary Islamic legal discourse and serve as a reference for society in understanding the proportional boundaries of bribery law.